The Impact of the SEC’s Office of Minority and Women Inclusion: Evidence from the Filing Review Process - Johnson, Bret A.; Kubic, Matthew; Lisic, Ling Lei; Wang, Mengmeng (The Accounting Review, 2026)
ABSTRACT We examine the impact of the SEC’s Office of Minority and Women Inclusion (OMWI) on the role of employee gender in the Division of Corporation Finance’s filing review process. Gender bias theory suggests that women may work harder to compensate for perceived bias and discrimination. Consistent with this theory, we find that women reviewers issue longer comment letters, raise more issues, ask more accounting-specific questions, reference more authoritative guidance, request more filing amendments, follow up on more issues from prior rounds, and take longer to close the comment letter process. We also find that women are less prevalent in higher paygrades and leadership positions. These gender differences attenuate after the establishment of OMWI in 2011, but significant differences remain. Analyses of SEC employee survey data corroborate our comment letter results. Data Availability: All data are publicly available. JEL Classifications: G18; J16; M48.